Pengaruh Return on Assets (ROA) dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sub-Sektor Makanan dan Minuman di BEI - Uliarta, Magdalena; Hasanuh, Nanu (Peneliti.net, 2025)
This study aims to examine the influence of Return on Assets (ROA) and firm size on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research employed a quantitative approach with descriptive and verifikatif methods using secondary data obtained from audited financial reports. A total of 25 companies were selected through purposive sampling, resulting in 100 panel data observations. The analysis was conducted using multiple linear regression. The results show that ROA has a significant positive effect on firm value, with a t-value of 4.213 and a significance level of 0.000 (<0.05), indicating that profitability increases market valuation. Firm size also has a significant positive effect on firm value, with a t-value of 2.698 and a significance level of 0.008 (<0.05), suggesting that larger firms tend to gain higher market confidence. The coefficient of determination (Adjusted R²) is 0.473, meaning that ROA and firm size together explain 47.3% of the variation in firm value. These findings imply that both profitability and firm scale are key indicators in evaluating the market value of companies in this sector.